TELAAH CELAH PEMENUHAN PIDANA DENDA DALAM PENEGAKAN HUKUM BAGI PENGEDAR NARKOTIKA - Wiwik Diah Muliasih; Itok Dwi Kurniawan (Sebelas Maret University, 2023)
The severity of the crimes imposed in narcotics crimes is in fact unable to eradicate its circulation and illicit trafficking. The purpose ofthe study was to examine the loopholes in the fulfillment of criminal fines for narcotics dealers in Decision Number: 19/Pid.Sus/2022/PN Krg. Themethod usedis normative legal research. The results of the research study show that the sentence imposedinaquocaseis in accordance with the provisions of the criminal procedure law in the Criminal Procedure Code. Nevertheless, the sentencing ruling that was handed down still seems to leave a loophole in sentencing, namely when the concept of imposing a finewith a substitute prison sentence causes a bad formulation because the purpose of the conviction is notappleto apple. In this case, the purpose of the fine is to deprive him of wealth while the penalty of imprisonment is aimed at depriving him of liberty. Such criticisms in particular can be observedin the lens of theoretical legal development and practical legal development.Keywords: Dealers; Fine; Narcotics Crimes